Год обезьяны: [повесть] / Чингиз Абдуллаев - Абдуллаев Чингиз Акифович (Абдуллаев, 2016)
Экземпляры: (20160415) / Инвентарный номер: 39158 / Цена: 223.00 / Сис.шифр: Р2 / Авт.знак: А 13 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6